2010
DOI: 10.1002/jssc.201000172
|View full text |Cite
|
Sign up to set email alerts
|

Determination of partition coefficient and analysis of nitrophenols by three‐phase liquid‐phase microextraction coupled with capillary electrophoresis

Abstract: A three-phase hollow fiber liquid-phase microextraction method coupled with CE was developed and used for the determination of partition coefficients and analysis of selected nitrophenols in water samples. The selected nitrophenols were extracted from 14 mL of aqueous solution (donor solution) with the pH adjusted to pH 3 into an organic phase (1-octanol) immobilized in the pores of the hollow fiber and finally backextracted into 40.0 microL of the acceptor phase (NaOH) at pH 12.0 located inside the lumen of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…To investigate the effect of sample volume, different volume (5,6,7,8,9, and 10 mL) of sample were studied. It was found that the largest analytical response was obtained when 6 mL of sample solution was used.…”
Section: Effect Of the Extraction Time And Sample Volumementioning
confidence: 99%
See 1 more Smart Citation
“…To investigate the effect of sample volume, different volume (5,6,7,8,9, and 10 mL) of sample were studied. It was found that the largest analytical response was obtained when 6 mL of sample solution was used.…”
Section: Effect Of the Extraction Time And Sample Volumementioning
confidence: 99%
“…Up to now, various pretreatment techniques have been developed to extract phenolic compounds from aqueous samples, such as solid-phase extraction (SPE) [5], solidphase microextraction (SPME) [6][7][8], single-drop microextraction (SDME) [3] and hollow-fiber liquid-phase microextraction (HF-LPME) [9]. However, SPE requires large volumes of toxic solvent, and the process is complicated and time-consuming [10].…”
Section: Introductionmentioning
confidence: 99%
“…The partition coefficient of the labeled complexes was measured separately by determining the partition coefficients between the organic and aqueous phases (18). From the solution of the labeled compound, 0.1 mL was added to a biphasic mixture of 1.9 mL of water and 2 mL of n-octanol, respectively.…”
Section: Partition Coefficientmentioning
confidence: 99%
“…HF-LLLME with NaOH as the acceptor solution has been widely used for the determination of acidic analytes [30][31][32][33]. However, if an organic alkali reagent is used instead of NaOH, it can not only be an acceptor solution for the extraction of acidic analytes owing to its alkalinity but also a derivatization reagent for the acidic analytes in the GC injection port at the same time.…”
Section: Introductionmentioning
confidence: 99%